WATTPAD AS A STORY-SHARING WEBSITE: IS IT A FIELD OF LITERARY PRODUCTION? - M. Yuseano Kardiansyah (Universitas Muhammadiyah Semarang, 2019)
This article investigates the existence of Wattpad as a cyber-platform to produce literary works through socio-cultural paradigm. By adopting Pierre Bourdieu’s theoretical framework, the discussion is intended to further elaborate whether such a story-sharing website – firstly launched in 2006 – has some typical natures as the field of literary production. The objective of this study is to explore how currently the influence of technological reformation is toward the practice of literary production. Eventually, from the exploration conducted to Wattpad, it is found that there are some typical characteristics that bring consideration to see it as a field of literary production. However, those characteristics must be seen contextually for it is conditioned in cyber space, yet the logic of conventional practice is carried over into it.